rSK1 in Rat Neurons: A Controller of Membrane rSK2? - Autuori, Eleonora; Sedlak, Petra; Xu, Li; C. Ridder, Margreet; Tedoldi, Angelo; Sah, Pankaj (Frontiers in Neural Circuits, 2019)
In mammalian neurons, small conductance calcium activated potassium channels (SK channels) are activated by calcium influx and contribute to the afterhyperpolarisation that follows action potentials. Three types of SK channel, SK1, SK2 and SK3 are recognised and encoded by separate genes that are widely expressed in overlapping distributions in the mammalian brain. Expression of the rat genes, rSK2 and rSK3 generates functional ion channels that traffic to the membrane as homomeric and heteromeric complexes. However, rSK1 is not trafficked to the plasma membrane, appears not to form functional channels, and the role of rSK1 in neurons is not clear. Here, we show that rSK1 co-assembles with rSK2. rSK1 is not trafficked to the membrane but is retained in a cytoplasmic compartment. When rSK2 is also present, heteromeric rSK1-rSK2 channels are also retained in the cytosolic compartment, reducing the total SK channel content on the plasma membrane. Thus, rSK1 appears to act as chaperone for rSK2 channels and expression of rSK1 may control the level of functional SK current in rat neurons.